Branding Strategy Management of Halal Products in The Digital Era (Study on The Muslim Fashion Industry in Banjar Regency) - Rusdiana, Rusdiana (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Muslim fashion industry in Indonesia, including in Banjar Regency, has experienced significant growth in recent years, especially in the digital era. Along with the increasing public awareness of halal products, the development of halal product brands in the Muslim fashion industry has become an important thing. This article aims to analyze the management of halal product branding strategies in the digital era, focusing on the Muslim fashion industry in Banjar Regency. Through a qualitative approach with case studies, this study identifies the branding strategies implemented by Muslim fashion industry players in Banjar Regency, the challenges faced, and how to utilize digital technology to increase competitiveness and market exposure. The results of the study indicate that strong brand management, effective communication through social media, and the use of the right digital platforms are the keys to success in branding halal products in the Muslim fashion industry. This study also provides recommendations for Muslim fashion business actors in optimizing branding strategy management in the digital era.